The Quest for Academisation of Intelligence Studies in Nigerian Universities: Resolving the Training Imbroglio of National Security Personnel - Awwal Isa; Ngboawaji Daniel Nte; Clairmont Roger Featherstone; Abdulaziz Baba Ahmadu (Indonesian National Police Academy, 2021)
Contemporary global and national security challenges have necessitated the need to widen the horizon of intelligence studies education across the world. For the seemingly advanced democracies of the West, this has created massive liberalisation of the quest for intelligence education and training in traditional and non-military universities. For the developing albeit transitional democracies, this quest is even more compelling as they face extreme national security challenges by non-state actors, widening ungoverned spaces, and the challenges of democratic penetration. Consequently, this work attempts to evaluate the challenges and prospects of consolidating intelligence studies for national security by universities in Nigeria. Relying on extensive qualitative research, the paper was able to evaluate these prospects and challenges with the eventual policy recommendations in the collective search for a sustainable national intelligence culture via formal education and training in Nigerian universities.